CoCrFeMnNi high‐entropy alloy powder with excellent corrosion resistance and soft magnetic property prepared by gas atomization method. Issue 7 (11th July 2019) - Jin, X.; Gu, X.; Quan, F.; Ran, X.; Zhang, K.; Mao, A.
Abstract: To successfully fabricate high‐entropy alloys by powder metallurgy, laser cladding, or thermal sprayed method, the high‐entropy alloy powders possessing good homogeneous microstructure are very important. However, the study on the properties of the high‐entropy alloy powder has still been lacking. In this work, an equiatomic CoCrFeMnNi high‐entropy alloy powder with spherical shape was synthesized by gas atomization method. The as‐atomized CoCrFeMnNi high‐entropy alloy powder is composed of a single face‐centered cubic solid solution phase with the particle size of 34.0 μm. Furthermore, the as‐atomized powder exhibits excellent corrosion resistance in 10 % hydrochloric acid solution to 304 L stainless steel powder, and also shows an excellent soft magnetic behavior. Therefore, the gas atomization method can be used to generate other kinds of high‐entropy alloy powders for many challenging industrial applications.